Sickness Presenteeism, Sickness Absenteeism, and Health Following Restructuring in a Public Service Organization - Caverley, Natasha; Cunningham, J. Barton; MacGregor, James N. (Journal of Management Studies, 2007)
abstract This study examined the relationship between sickness presenteeism, sickness absenteeism, organizational outcomes and employee health. In particular, we wanted to investigate to what degree employees were substituting sickness presence for sickness absence. Three hypotheses were tested to formalize this ‘substitution proposition’. We surveyed a Canadian public service organization which was involved in a large scale downsizing initiative. For this study, 237 Personnel Corporation (pseudonym used) employees responded to the survey, representing a 66 per cent response rate. Survey results indicated that, while the workforce was of average health, sickness absenteeism was less than half that of the national average. The difference could be accounted for by sickness presenteeism – the average number of days employees attended work while ill or injured was greater than the number of days of sickness absence. The pattern of results supported the notion that employees were substituting presenteeism for absenteeism. The frequency and type of self‐reported health problems were highly similar for presenteeism and absenteeism. Work factors (e.g. job security, supervisor support and job satisfaction) tested were significantly correlated with presenteeism. Presenteeism appears to be a stronger predictor of health than absenteeism, suggesting that efforts to improve workplace health may have a more immediate impact on presenteeism than on absenteeism.